The Role of Physical Education in Building Students’ Soft Skills: A Literature Study - Insanistyo, Bayu; Pujianto, Dian; Hussein, Ali Radhi Abdul (The Indonesian Institute of Science and Technology Research, 2025)
Physical Education has a strategic role in developing students' physical fitness and building non-technical skills (soft skills) that are very much needed in the 21st century. The purpose of this study is to systematically examine the contribution of Physical Education in developing students' soft skills through literature studies. The research method uses the Systematic Literature Review (SLR) approach with PRISMA guidance. Data were collected from the Google Scholar and Scopus databases using the keywords